EVALUASI LAHAN PERSAWAHAN PADA TIGA DAERAH ALIRAN SUNGAI DI SUMATERA BARAT - Azwar Rasyidin (Jurnal Solum, 2009)
Research on  soils fertility of rice soils has been done on three catchment in West Sumatra province ie; Ulu Selo ( inland areas of selo river) at Tanah Datar district conducted three Kenagarian ( traditional village) Simpurut, Gurun, and Padang Laweh.  Lembang catcment at Solok district is conducted ubo irrigation scheme ubo which divided as Ubo atas irrigation scheme and Sirukam. Sumpur cathment at East Pasaman District conducted three  Kenagarian, Lundar, Petok and Kuamang.  All of irrigation scheme located at agroclimatic zone C1 up to D2, with charaterize 2 or 3 consecutive  wet month  and 3 or 4 consecutive dry month. Soils were developed from volcanic parents materials.  Rice soils of Ulu Selo  shown lower pH value compared to the soils with land use is mixed garden, which some of the sampling point has shown the pH lower than 4. the rice soils of Lembang and Sumpur also shown the similar trend of pH but the value not so extremely like the soils from Ulu Selo. Related to the minimum value of carbon in rice soils is indicate that some  of the rice soils in the research areas could be grouping as degraded land.  The rice soils from Sumpur has high natural soil fertility which which shown on the natural reserved of nitrogen, phosphor and potassium. The soils condition could support the rice production up to 8t/ha/ GS without additional nutrient. While soils from Ulu Selo shown lower content of phosphor. Based on this research author suggested to fertilizer program is better done based on the condition of soils itself. Even the natural soils fertility is high is not reccomended to use addtional artificials fertilizer.Key words: cathment studies, natural soil fertility, rice production and land degradation.